Efek flavonoid daun srikaya (Annona squamosa (L)) terhadap pemacuan ekspresi P53 sel HeLa - Laela Hayu Nurani; Suwidjiyo Pramono; Sudjadi . (Indonesian Journal of Pharmacy, 2011)
Flavonoids  are  secondary  metabolites  with  many  activities  such  as  an anticancer  and  an  antioxidant. Annona  squamosa L.  leave  are  reported  contain flavonoids. Annona squamosa flavonoids were isolated from ether fraction and separated by paper chromatography with acetic acid 15% as mobile phase. Four flavonoids   with  Rf  value  of  0.11,  0.23,  0.46  and  0.78  were  detected  as  5-hydroxy-7-R-flavonol  (1),  5,3’,4’-trihydroxy-7-R-flavonol  (2),  5-hydroxy-7-Rflavanone  (3)  and  7-R-flavanone  (4),  respectively.  The  cytotoxicity  of  each flavonoid  on  Hella  cell  line  was  carried   out   using  direct  counting  method  and the p53 expression was done with immunocytochemistry. The result showed that LC50  of  flavonoid 1, 2, 3 and  4 was  12.63±3.4,  18.47±3.4,  75.74±6.2  and 204.4±14.0  µg/mL.   Twelve   µg/mL  of  5-hydroxy-7-R-flavonol  (1)   increased p53 expression of eleven fold than control.Keywords: Annona squamosa, HeLa, flavonoid, p53